N-rich chitosan-derived porous carbon materials for efficient CO2 adsorption and gas separation - Min, Han; Zhang, Ke; Guo, Zhongya; Chi, Fengyao; Fu, Lili; Li, Bin; Qiao, Xueyi; Wang, Shuang; Cao, Shaokui; Wang, Bing; Ma, Qingxiang (Frontiers in Chemistry, 2023)
Capturing and separating carbon dioxide, particularly using porous carbon adsorption separation technology, has received considerable research attention due to its advantages such as low cost and ease of regeneration. In this study, we successfully developed a one-step carbonization activation method using freeze-thaw pre-mix treatment to prepare high-nitrogen-content microporous nitrogen-doped carbon materials. These materials hold promise for capturing and separating CO2 from complex gas mixtures, such as biogas. The nitrogen content of the prepared carbon adsorbents reaches as high as 13.08 wt%, and they exhibit excellent CO2 adsorption performance under standard conditions (1 bar, 273 K/298 K), achieving 6.97 mmol/g and 3.77 mmol/g, respectively. Furthermore, according to Ideal Adsorption Solution Theory (IAST) analysis, these materials demonstrate material selectivity for CO2/CH4 (10 v:90 v) and CO2/CH4 (50 v:50 v) of 33.3 and 21.8, respectively, at 1 bar and 298 K. This study provides a promising CO2 adsorption and separation adsorbent that can be used in the efficient purification process for carbon dioxide, potentially reducing greenhouse gas emissions in industrial and energy production, thus offering robust support for addressing climate change and achieving more environmentally friendly energy production and carbon capture goals.